Retrieval action of zinc and folic acid for the restoration of normal reproductive function in bisphenol-A exposed male albino mice - Mustari, Afrina; Alam, Mahabub; Miah, Mohammad Alam; Nooruzzaman, Mohammed; Sujan, Khaled Mahmud; Chowdhury, Emdadul Hauqe (Veterinarni medicina, 2022)
Bisphenol-A (BPA) has become a great concern due to its toxic effects. The present study investigated the retrieval action of zinc (Zn) and folic acid (FA) supplementation against BPA-induced reproductive toxicities in male albino mice. A total of seventy-five 25-28 day-old mice were divided into five equal groups (group A-E, 15 mice in each group). The mice were given normal rations (control, group A) or administered with daily doses of BPA at 50 mg/kg body weight (b.w.) (group B-E). The mice from groups C, D and E were supplemented with Zn (10 mg/kg b.w.), FA (3 mg/kg b.w.) and both in the feed, respectively, daily for 12 weeks. Blood samples were collected, and the sera were separated for biochemical and hormonal analyses. The standard method was followed to test the sperm motility and sperm count. The testis samples were processed for a routine histopathological study using haematoxylin and eosin staining. The sperm counts, motility, and serum testosterone significantly declined in the BPA-exposed animals, but dramatically increased after the Zn and FA supplementation. There was significant degeneration of the seminiferous tubules in the testes of the BPA-exposed mice, which was recovered moderately by the Zn and FA supplementation. The study shows the retrieval action of zinc and folic acid in the restoration of normal reproductive function in bisphenol-A exposed male mice.
Keywords: histopathology; hormone; reproduction; biochemical; BPA